2021
DOI: 10.1186/s12877-021-02013-3
|View full text |Cite
|
Sign up to set email alerts
|

Age is not the only risk factor in COVID-19: the role of comorbidities and of long staying in residential care homes

Abstract: Background The actual SARS-CoV-2 outbreak caused a highly transmissible disease with a tremendous impact on elderly people. So far, few studies focused on very elderly patients (over 80 years old). In this study we examined the clinical presentation and the outcome of the disease in this group of patients, admitted to our Hospital in Rome. Methods This is a single-center, retrospective study performed in the Sant’Andrea University Hospital of Rome.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 32 publications
6
40
0
Order By: Relevance
“…An important reason why advanced age contributes to morbidity is the increased frequency of comorbid conditions. 17 In our study, we found that the frequency of general comorbidity increased significantly from the asymptomatic disease group to the severe disease group, concurrent with age. We also found that DM and ischemic heart disease are significant risk factors for severe disease among all comorbid conditions.…”
Section: Discussionsupporting
confidence: 50%
“…An important reason why advanced age contributes to morbidity is the increased frequency of comorbid conditions. 17 In our study, we found that the frequency of general comorbidity increased significantly from the asymptomatic disease group to the severe disease group, concurrent with age. We also found that DM and ischemic heart disease are significant risk factors for severe disease among all comorbid conditions.…”
Section: Discussionsupporting
confidence: 50%
“…Thus, when calculating the risk difference between mortality of COVID-19 and non-COVID-19 patients, the rate of 26.2% appears similar to the overall fatality rate of 24.3% described for female patients aged between 80 and 89 years in Italy during the “first wave” [ 35 ], which is a demographic profile similar to the present study. Accordingly, further studies should be aimed at identifying if the HF itself represents a risk factor of increased mortality in patients with COVID-19, as demonstrated for obesity, neoplastic diseases, and diabetes [ 36 , 37 , 38 , 39 ], as the opposite situation (COVID-19 as a risk factor for HF patients) seems a piece of consolidated evidence [ 16 , 32 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term health care facilities such as nursing homes and rehabilitation centres provide care to persons often of elderly age and with mental or physical impairment. The residents of long-term care homes represent a vulnerable population with a greater risk of adverse events and infections due to age, comorbidities, and living in close proximity to other persons [ 5 ]. Therefore, different international organisations recommended that long-term care facilities should adopt special measures to protect their residents, staff, and visitors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%